Altered Disrupted-in-Schizophrenia-1 Function Affects the Development of Cortical Parvalbumin Interneurons by an Indirect Mechanism - Borkowska, Malgorzata (PLoS One, 2016)
Disrupted-in-Schizophrenia-1 (DISC1) gene has been linked to schizophrenia and related major mental illness. Mouse Disc1 has been implicated in brain development, mainly in the proliferation, differentiation, lamination, neurite outgrowth and synapse formation and maintenance of cortical excitatory neurons. Here, the effects of two loss-of-function point mutations in the mouse Disc1 sequence (Q31L and L100P) on cortical inhibitory interneurons were investigated. None of the mutations affected the overall number of interneurons. However, the 100P, but not the 31L, mutation resulted in a significant decrease in the numbers of interneurons expressing parvalbumin mRNA and protein across the sensory cortex. To investigate role of Disc1 in regulation of parvalbumin expression, mouse wild-type Disc-1 or the 100P mutant form were electroporated in utero into cortical excitatory neurons. Overexpression of wild-type Disc1 in these cells caused increased densities of parvalbumin-expressing interneurons in the electroporated area and in areas connected with it, whereas expression of Disc1-100P did not. We conclude that the 100P mutation prevents expression of parvalbumin by a normally sized cohort of interneurons and that altering Disc1 function in cortical excitatory neurons indirectly affects parvalbumin expression by cortical interneurons, perhaps as a result of altered functional input from the excitatory neurons.